7-Isopenthenyloxycoumarin, Arctigenin, and Hesperidin Modify Myeloid Cell Leukemia Type-1 (Mcl-1) Gene Expression by Hormesis in K562 Cell Line. Issue 3 (11th September 2018) - Kafi, Zahra; Cheshomi, Hamid; Gholami, Omid
Hormesis is a new concept in dose–response relationship. Despite of traditional dose–response curves, there is a low-dose stimulation and a high-dose inhibition in this case. Hormesis effect in apoptosis induction/inhibition by natural compounds is reported previously. Here, we searched this effect for myeloid cell leukemia type-1 (Mcl-1) gene expression by phytochemicals 7-isopenthenyloxycoumarin (7-IP), arctigenin (Arg), and hesperidin (Hsp). For this purpose, first we tested the cytotoxicity of various doses of these compounds against K562 leukemia cell lines for different times by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide method. After that we explored the effect of various doses of these phytochemicals on Mcl-1 gene expression for different times by real-time polymerase chain reaction method. We found that these phytochemicals have cytotoxicity against K562 cell line. Hesperidin is the most cytotoxic agent. We also found that these natural compounds have hormetic effect on Mcl-1 gene expression. The hormetic model in Mcl-1 gene expression is overcompensation stimulation. This phenomenon is reported for the first time. We conclude that 7-IP, Arg, and Hsp are cytotoxic against K562 cancerous cells and induce/inhibit Mcl-1 gene expression by hormesis dose–response relationship.